The Relationship between Unilateral Palatal Maxillary Canine Impaction and the Morphology of the Maxilla: A CBCT Study in Eastern Province of Saudi Arabia - Shahin, Suliman Y.; Tabassum, Afsheen; Fairozekhan, Arishiya Thapasum; Tuwaylib, Ahmed Al; Al-Sheyoukh, Saeed; Alzaher, Shuaib; Siddiqui, Intisar Ahmad; Alhareky, Muhanad (European Journal of Dentistry, 2022)
Objective This study aimed to examine the correlation between the morphology of the maxilla and unilateral palatally impacted maxillary canine (PIMC) among the Saudi population in the Eastern Province of Saudi Arabia.Materials and Methods In this retrospective study, 36 patients' records [(17 PIMC, 8 male, 9 female, mean age 16.75 ± 2.12 years) (19 control; 9 male,10 female, mean age: 17.16 ± 2.12 years)] were included from a teaching dental hospital. On cone-beam computed tomographic images, measurements of maxillary arch length (MAL), palatal vault depth (PVD), intermolar width, sum of widths of 4 maxillary incisors, available arch space (AAS), palatal maxillary width (PMW) in the molar and premolar regions, nasal cavity width (NCW), maxillary arch shape (MAS) (arch length/intermolar width x 100), and palatal vault shape (PVS) (the PVD/intermolar width x100) were performed. Data were analyzed by SPSS-20.0. p-value less than or equal to 0.05 reflected statistical significance.Results This study's findings depicted that AAS (p = 0.012), PVD (p = 0.028), and PMW in the molar and premolar regions at the level of the alveolar crest (p = 0.002 and p = 0.034) and mid-root (p = 0.004 and p = 0.022) were significantly higher in the control compared to the PIMC group. PVS showed a significant difference between the PIMC and control groups (p = 0.037). However, regarding MAS, no significant difference was observed (p = 0.707).Conclusion MAS was narrower in PIMC compared to the control group. The control group had a deeper palatal vault and greater AAS compared to the PIMC group. However, no significant difference was observed between groups regarding tooth size or NCW.
Keywords: CBCT; palatally impacted maxillary canine; morphology of the maxilla; canine impaction; retrospective study